Review of the Causes of 1907 Panic and Aftermath - Ramjerdi, Maria Hamideh (Journal of Reviews on Global Economics, 2020)
The Panic of 1907 is often known as the Panic that initiated the development of the Federal Reserve System (Bordo, 1985). The Panic of 1907 was â€œThe beginning of the end of unregulated capital markets and banking system without the lender of the last resort in the United States.â€ (Fohlin, Gehrig and Haas, 2015, page 2). Numerous causes lead to the Panic of 1907 including: shadow banking, the San Francisco earthquake and fire, stock price manipulation, seasonal agriculture fluctuations, an outflow of gold, and higher interest rates. This paper reviews the primary literature on these causes, and how they led to the Panic of 1907 and the subsequent regulations culminating in the Federal Reserve Bank.